Phytoremediation: a property of plant to clean up our environment (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
This review presents the idea of phytoremediation which is a generic term given to a set of technologies that uses different plants to contain, extract, degrade or immobilize contaminants from soil and water. Being a cost saving procedure compared to conventional treatments it has become an interesting method in remediation technology. Moreover, for developing countries like Bangladesh, along with the cost effectiveness, phytoremediation is also suitable for its environmental friendly and aesthetically pleasing approach. This paper reports about the mobility, bioavailability and plant response to the presence of harmful contaminants in our environment. It also gives an insight into the work done by authors, which focuses on modifying plants to have increased phytoremediation properties, studying the expression profile of miRNAs and their target genes responsible for phytoremediation. Thus, this paper attempted to provide a concise review on recent progresses in research and convenient applications of phytoremediation for environmental resources.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 156-160